Anti-seizure medication exposure and the risk of dementia: A meta-analysis of observational studies - Zhang, Lei; Jiang, Hai-yin; Liu, Wen-juan (Frontiers in Neurology, 2023)
Objective: There is growing evidence of a relationship between antiepileptic drug (AED) use and the risk of dementia. This study examined this association using a meta-analysis approach. Methods: PubMed, EMBASE, and Cochrane Library were systematically searched for studies published in English only. Study quality was evaluated using the Newcastle-Ottawa Scale, and an overall odds ratio (OR) was pooled using fixed or random-effects models. Results: The analysis included 9 articles with 10 studies. The results showed that overall AED exposure was associated with an increased risk of dementia (OR: 1.08, 95% confidence interval [CI]: 1.03–1.14; P = 0.002). However, this association disappeared (OR: 1.02, 95% CI: 0.97–1.07; P = 0.361) when the study data adjusted for drug indications were pooled. Subgroup analysis based on individual drugs found only a positive association among those exposed to valproate, carbamazepine, and clonazepam. A more pronounced risk was observed in patients with bipolar disorder exposed to AEDs (OR: 1.43, 95% CI: 1.07–1.92; P = 0.015; I2 = 85.9%). Conclusions: First-generation AEDs might be associated with an increased risk of dementia. Future well-designed studies considering AED indications are needed to verify our findings.